2016
DOI: 10.1177/0886260515585528
|View full text |Cite
|
Sign up to set email alerts
|

The View From the Bottom

Abstract: We investigated the relation between relative deprivation (RD)-disparity in affluence between adolescents and their more affluent schoolmates-and involvement in bullying among 23,383 students (aged 9-19) in 413 schools that participated in the 2010 Canadian Health Behavior in School-Aged Children survey. Students reported family affluence and frequency of bullying victimization and perpetration during the previous 2 months. Using the Yitzhaki index of RD and multinomial logistic regression analysis, we found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 45 publications
(76 reference statements)
1
12
2
Order By: Relevance
“…Similar to other racial and ethnic groups, bullying victimization at school was also shown to be positively associated with cyberbullying victimization. Our findings also indicate that “quite well off” family socioeconomic status was associated with a lower risk of cyberbullying victimization, which is consistent with past research findings (Napoletano et al, 2016; Sykes et al, 2017). On the contrary, “very well off” family socioeconomic status had a higher risk of cyberbullying victimization, which is in line with Topçu et al’s (2008) findings.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similar to other racial and ethnic groups, bullying victimization at school was also shown to be positively associated with cyberbullying victimization. Our findings also indicate that “quite well off” family socioeconomic status was associated with a lower risk of cyberbullying victimization, which is consistent with past research findings (Napoletano et al, 2016; Sykes et al, 2017). On the contrary, “very well off” family socioeconomic status had a higher risk of cyberbullying victimization, which is in line with Topçu et al’s (2008) findings.…”
Section: Discussionsupporting
confidence: 93%
“…Although parental awareness and monitoring are protective factors for White youth, for Black and minority youth, they tend to show a higher rate of social media usage (Edwards et al, 2016); as a result, they might have the know-how to avoid cyberbullying victimization even without the presence of their parents who are working. Alternatively, Black youth whose parents are employed might be at a lower risk of cyberbullying victimization as they are less likely to be impoverished, which has been found to be associated with bullying victimization (Jansen et al, 2012; Napoletano et al, 2016; Tippett & Wolke, 2014; Zhang et al, 2020). More research on the role of parental employment as a proxy for economic and social conflicts within the family systems and how they might relate to adolescents’ bullying and cyberbullying victimization experiences is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Guided by the social-ecological perspective, the study also explored correlates of bullying victimization across Black/White biracial, White, and Black adolescents. For biracial youth, our findings indicated that family affluence was positively related to bullying victimization, contrary to other studies that showed that youth of higher family socioeconomic status are less likely to be bullied (Napoletano et al, 2016). Although we were unable to locate research evidence, biracial adolescents of higher family socioeconomic status might be perceived as "different" by their peers, particularly their peers of lower family socioeconomic status, which could reinforce resentments and increase their risk of bullying victimization.…”
Section: Black/white Biracial Adolescentscontrasting
confidence: 99%
“…This leads these individuals and groups to develop negative emotions, such as anger and resentment (H. J. Smith et al, 2012; Xuan et al, 2021). Although relative deprivation is an important influencing factor for aggression (e.g., Greitemeyer & Sagioglou, 2017; Kassab et al, 2021), only one study has found that relative deprivation was associated with cyberbullying (Napoletano et al, 2016). The temporal sequence effect and possible mediating mechanisms underlying the effect remain unclear.…”
Section: Introductionmentioning
confidence: 99%